Mitochondria Present in Excised Patches From Pancreatic B-cells May Form Microcompartments With ATP-Dependent Potassium Channels. Issue 2 (April 1999) - Rustenbeck, I.; Dickel, C.; Herrmann, C.; Grimmsmann, T.
Abstract : Experiments with inside-out patches excised from pancreatic B-cells have yielded evidence that mitochondria are often contained in the cytoplasmic plug protruding into the tip of patch pipette. When intact B-cells were loaded with the fluorescent mitochondrial stain, rhodamine 123, and membrane patches excised from these cells, a green fluorescence could be observed in the lumen at the tip of the patch pipette. The same result was obtained with the mitochondrial stain, MitoTracker Green FM, which is only fluorescent in a membrane-bound state. Furthermore, the open probability of ATP-dependent potassium (KATP ) channels in inside-out patches was influenced by mitochondrial fuels and inhibitors. Respiratory substrates like tetramethyl phenylene diamine (2 mM) plus ascorbate (5 mM) or α-ketoisocaproic acid (10 mM) reduced the open probability of KATP channels in inside-out patches significantly (down to 57% or 65% of control, respectively). This effect was antagonized by the inhibitor of cytochrome oxidase, sodium azide (5 mM). Likewise, the inhibitor of succinate dehydrogenase, malonate (5 mM), increased the open probability of KATP channels in the presence of succinate (1 mM). However, oligomycin in combination with antimycin and rotenone did not increase open probability. Although it cannot be excluded that these effects result from a direct interaction with the KATP channels, the presence of mitochondria in the close vicinity permits the hypothesis that changes in mitochondrial metabolism are involved, mitochondria and KATP channels thus forming functional microcompartments.